The Combined Effect of Brand Gestalt, Brand Awareness, and Brand Image on Ecotourism WOM Intention - Mandagi, Deske W.; Pasuhuk, Lefrand S.; Kainde, Sandra J.R. (Penerbit Goodwood, 2024)
Purpose: This study aims to critically examine the interplay of brand gestalt, brand awareness, and brand image in the rapidly evolving context of ecotourism destinations, addressing the immediate need for insights that can enhance sustainable tourism marketing strategies. Methodology: A quantitative research design was utilized in this study using survey-based data on 241 respondents who were visitors to ecotourism destinations in North Sulawesi, Indonesia. Results: This study found that service quality, platform type, shopping convenience, and product quality have a positive influence on consumer satisfaction when shopping online. Limitations: One potential limitation of the study is that the respondents were limited to customers of online shoppers and college students in North Sulawesi, which may restrict the generalizability of the findings to broader consumer populations. Contribution: Tourism operators can use the insights gained from this study to enhance their brand strategy. By focusing on building a strong brand gestalt, increasing brand awareness, and fostering a positive brand image, they can effectively stimulate WOM, which is a powerful marketing tool in ecotourism.